Nutrient removal using biofilm reactor with support media - Shahrul Amri, Shafie @ Safie (2009)
The phosphorus removal becomes very important nowadays in order to reduced eutrophication. The aim of this study is to find the suitable loading rate for the highest phosphorus removal efficiency using biofilm reactor. Experiments are carried out in eight sequencing batch reactors (SBRs) at hydraulic retention time (HRT) of 5 d. This experiment is operated at loading rates of 5.0, 4.5, 4.0, 3.5 and 3.0 mg/L.d. The biofilm growth is increased with the increasing of loading rate according to the suspended solids readings. Loading rate 5 mg/L.d shows the highest suspended solid concentration which is 1585 mg/L at average reading. The Phosphorus removal efficiency was increasing according to the increasing of loading rate while the chemical oxygen demand (COD) removal is decreased with the increasing of loading rates. The loading rate 5.0 mg/L.d shows the highest average removal efficiency ranged from 66% to 87%. The COD removal is highest at loading rate 3.5 mg/L.d with 83% of average removal. The removal efficiency was influenced by the biofilm growth according to the suspended solid readings. The highest suspended solids reading give the highest removal efficiency. According to the Design Expert plotted, the highest predicted phosphorus removal can be achieved at loading rate 5.0 mg/L.d with 72.53% of phosphorus removal, 76.14% COD removal and 1142.85 mg/L of suspended solid (SS) concentration. The highest predicted COD removal can be achieved at loading rate (LR) 3.0 mg/L.d with 77% removal. The expected phosphorus removal is 66% and the expected suspended solid (SS) concentration is 984 mg/L. As the conclusion, the mixed culture from soil is capable of degrading phosphorus at which the effective loading rate is 5.0 mg/L.d.